Non-invasive ventilation in acute respiratory failure: a randomised comparison of continuous positive airway pressure and bi-level positive airway pressure. Issue 6 (17th November 2003) - Cross, A M; Cameron, P; Kierce, M; Ragg, M; Kelly, A-M
Abstract : Objectives: To determine whether there is a difference in required duration of non-invasive ventilation between continuous positive airway pressure (CPAP) and bi-level positive airway pressure (BiPAP) in the treatment of a heterogeneous group of emergency department (ED) patients suffering acute respiratory failure and the subgroup of patients with acute pulmonary oedema (APO). Secondary objectives were to compare complications, failure rate, disposition, length of stay parameters, and mortality between the treatments. Methods: This prospective randomised trial was conducted in the emergency departments of three Australian teaching hospitals. Patients in acute respiratory failure were randomly assigned to receive CPAP or BiPAP in addition to standard therapy. Duration of non-invasive ventilation, complications, failure rate, disposition, length of stay (hospital and ICU), and mortality were measured. Results: 101 patients were enrolled in the study (CPAP 51, BiPAP 50). The median duration of non-invasive ventilation with CPAP was 123 minutes (range 10–338) and 132 minutes (range 20–550) for BiPAP (p = 0.206, Mann-Whitney). For the subgroup suffering APO, 36 were randomised to CPAP and 35 to BiPAP. For this group the median duration of non-invasive ventilation for CPAP was 123 minutes (range 35–338) and 133 minutes (range 30–550) for BiPAP (p = 0.320, Mann-Whitney). Conclusions: These results suggest that there is no significant difference in the duration of non-invasive ventilation treatment between CPAP and BiPAP when used for the treatment of acute respiratory failure in the ED. There was also no significant difference between the groups in secondary end points.